PENGARUH ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED TERHADAP RETURN SAHAM PADA PERUSAHAAN INDUSTRI SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Fauziah, Gina; Amelia, Rizka Wahyuni (Journal of Research and Publication Innovation, 2024)
This study aims to determine the partial and simultaneous effects of Economic Value Added (EVA) and Market Value Added (MVA) on stock returns in food and beverage sub-sector industrial companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The research method uses a quantitative approach. The research population includes 84 food and beverage sub-sector industrial companies listed on the IDX during the 2018-2022 period, with a sample of 5 food and beverage sub-sector industrial companies listed on the IDX during the 2018-2022 period selected through purposive sampling method. The data used is secondary data, which is collected through documentation and literature studies. Data analysis was carried out with descriptive statistics, selection of panel data regression estimation models, classical assumption tests, panel data regression tests, and coefficient tests using EViews version 12. The results showed that EVA partially had no significant effect on stock returns (Prob. value 0.714> 0.05, tcount 0.371 < ttable 2.074). Meanwhile, MVA partially has a positive and significant effect on stock returns (Prob value. 0.0005 <0.05, tcount 4.066> ttable 2.074). Simultaneously, EVA and MVA have a positive and significant influence on stock returns by 37,8%, while 62,2% is influenced by other variables not examined (Prob value. 0.002 < 0.05; fcount 8.305 > ftabel 3.443).